Integration of HIV Care into Community Management of Acute Childhood Malnutrition Permits Good Outcomes: Retrospective Analysis of Three Years of a Programme in Lusaka. - Beatrice Amadi; Mercy Imikendu; Milika Sakala; Rosemary Banda; Paul Kelly (PLoS ONE)
Background While HIV has had a major impact on health care in southern Africa, there are few data on its impact on acute malnutrition in children in the community. We report an analysis of outcomes in a large programme of community management of acute malnutrition in the south of Lusaka. Programme activities and analysis Over 3 years, 68,707 assessments for undernutrition were conducted house-to-house, and children with severe acute malnutrition (SAM) or moderate acute malnutrition (MAM) were enrolled into either Outpatient Therapeutic Programme (OTP) or Supplementary Feeding Programme (SFP) respectively. Case records were analysed using tabulation and unconditional logistic regression. Findings 1,859 children (889 boys, 970 girls; median age 16 months) with MAM (n = 664) or SAM (n = 1,195) were identified. Of 1,796 children whose parents consented to testing, 185 (10.3%) were HIV positive. Altogether 1,163 (62.6%) were discharged as recovered from acute malnutrition. Case fatality while in the programme was 4.2% in children with SAM and 0.5% in those with MAM (RR of SAM 10.9; 95%CI 3.4,34.8; P<0.0001), and higher in children with HIV infection (RR 5.2, 95%CI 2.9, 9.0; P<0.0001). In multivariate analysis, HIV (OR 5.2; 95%CI 2.6, 10.1; P<0.0001), MUAC <11.5 cm (OR 4.1; 95%CI 2.2, 7.4; P<0.0001) and the first year of the programme (OR 1.9; 95%CI 1.0, 3.4; P = 0.04) all increased mortality. Children with HIV infection who were able to initiate antiretroviral therapy had lower mortality (RR 0.23; 95%CI 0.10, 0.57; P = 0.0008). Interpretation Our programme suggests that a comprehensive community malnutrition programme, incorporating HIV care, can achieve low mortality even in a population heavily affected by HIV.